(untitled) (GAIMS Journal of Medical Sciences, 2026)
Background: Infections of sterile body fluids are medical emergencies associated with high morbidity and mortality. Early identification of causative aerobic bacteria and their antimicrobial susceptibility patterns is crucial for timely, effective empirical therapy and for monitoring evolving antimicrobial resistance trends in tertiary care settings. The present study aims to evaluate the aerobic bacteriological profile and antimicrobial susceptibility pattern among isolates from sterile body fluids excluding blood. Material and methods: Cross-sectional study was carried out for a period of 1 year. Clinical specimens (pleural fluid, peritoneal fluid, cerebrospinal fluid, synovial fluid, pericardial fluid) were subjected to cultural analysis according to standard laboratory procedures. Antibiotic sensitivity testing was done by Kirby Bauer Disc diffusion method as per CLSI Guidelines [M100, 30th edition, 2020]. Results: Culture positivity rate was 14.83%. Highest positivity rate was seen in pleural fluid (27.55%), followed by synovial fluid (23.07%), peritoneal fluid (17.85%), CSF (4.79%) and no bacterial growth among pericardial fluids. The most predominant isolates were E. coli (22%), Pseudomonas spp. (20%), Klebsiella spp. (15%), Staphylococcus aureus (13%), Acinetobacter spp. (9%) and Enterococcus spp. (5%). Enterobacteriaceae were sensitive to meropenem, amikacin and piperacillin/tazobactam. Gram-positive-isolates were sensitive to vancomycin, linezolid. Pseudomonas spp. was sensitive to Polymyxin B, meropenem and piperacillin/tazobactam. Conclusion: Timely and appropriate antibiotic treatment; often empiric, can improve the clinical outcome of body fluid infections. Hence, Regular monitoring of prevalent pathogenic organisms and their sensitivities are essential.